Moderate drinking before the unit: medicine and life assurance in Britain and the US c.1860–1930 - Kneale, James; French, Shaun (Informa Healthcare, 2015)
This article describes the way in which “Anstie’s Limit” – a particular definition of moderate drinking first defined in Britain in the 1860s by the physician Francis Edmund Anstie (1833–1874) – became established as a useful measure of moderate alcohol consumption. Becoming fairly well-established in mainstream Anglophone medicine by 1900, it was also communicated to the public in Britain, North America and New Zealand through newspaper reports. However, the limit also travelled to less familiar places, including life assurance offices, where a number of different strategies for separating moderate from excessive drinkers emerged from the dialogue between medicine and life assurance. Whilst these ideas of moderation seem to have disappeared into the background for much of the twentieth century, re-emerging as the “J-shaped” curve, these early developments anticipate many of the questions surrounding uses of the “unit” to quantify moderate alcohol consumption in Britain today. The article will therefore conclude by exploring some of the lessons of this story for contemporary discussions of moderation, suggesting that we should pay more attention to whether these metrics work, where they work and why.